2020
DOI: 10.14710/ijred.2020.30286
|View full text |Cite
|
Sign up to set email alerts
|

CFD Investigation of A New Elliptical-Bladed Multistage Savonius Rotors

Abstract: The Savonius-conventional wind turbine is a class of wind turbines designed with a vertical axis. It has a good starting capacity and   an insensitivity to wind direction. It works relatively at low wind speed in an easy installation. Savonius wind turbine faces major drawbacks, including some of the low efficiency and high negative torque created by the returning blade. Many attempts have been undertaken to optimize the blade’s shape to increase the performance of these wind turbines. The vertical axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The aerodynamic efficiency of the turbine is defined by the power coefficient (Cp), which is the ratio of the power of the wind turbine and the power of the wind speed given in equations 7 -9 (Mrigua et al, 2020), (Zemamou et al, 2020).…”
Section: Savonius Wind Turbinementioning
confidence: 99%
“…The aerodynamic efficiency of the turbine is defined by the power coefficient (Cp), which is the ratio of the power of the wind turbine and the power of the wind speed given in equations 7 -9 (Mrigua et al, 2020), (Zemamou et al, 2020).…”
Section: Savonius Wind Turbinementioning
confidence: 99%
“…Zemamou et al (Zemamou et al, 2019) have developed a modified design based on elliptical shape with a straight trailing edge the modified design shows a maximum Cp of 0.335, whereas the conventional model indicates the highest Cp of 0.25. the utilization of the elliptical blades in multi-stage systems has been studied by Mrigua et al (Mrigua et al, 2020). It is found that the two stages rotor has a higher power coefficient than the single and three stage rotors.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, vertical axis cross-flow hydrokinetic turbines are suitable for a greater water depth. Savonius (Mrigua et al 2020) and Darrieus turbines (Yagmur et al 2021) As per the Energy statistical report -2021 released by the National Statistical Office (Government of India), India's total renewable energy reserve is 1,097,465 MW. Small hydropower constitutes only 1.93% (21,134 MW) of the reserve.…”
Section: Introductionmentioning
confidence: 99%